Patients that are having Covid-19 Disease After the First Dose of Covid-Vaccine - Hakan Sezgin Sayiner; Aşki Vural; Fatih Doğan; Sedat Parlak; Furkan Bakirhan (Medical Laboratory Technology Journal, 2021)
There is no effective treatment for the Covid-19 disease that is still impacting the whole world. It considered that vaccines, one of the effective means to prevent infectious diseases, will play a significant role in protecting from the Covid-19 Disease. Vaccinations generals performed before exposure. We aimed to follow the clinical and laboratory progress of patients who got Covid-19 after the first dose of the Covid-19 vaccine and to evaluate the changes that may occur in antibody formation. 13 patients, who received the first dose of COVID 19 vaccine Coronovac as of 14.01.2021 when vaccination started in Adıyaman University Training and Research Hospital/Turkey, who had symptoms after the vaccine and whose real-time PCR found to be positive, were included in the study. After the first dose of the Covid-19 vaccine, 13 patients exam. Three of our patients were female, and 10 of them were male. The average age was 38.8. British variant detected in 4 of our patients; 1 of them was female. Contact times differed between 3 and 5 days. The most common symptoms were muscle-joint pain (53.8), weakness-fatigue (46.2), fever (38.5), and headache (30.8). Three of our patients, being one female, received inpatient treatment. Furthermore, our five patients who checked regarding Sars cov-2 IgG became positive in the first month. No adverse changes in the course of the illness observed in the patients were RT-PCR positive after the first dose of the Covid-19 vaccine. Antibody response detected at the end of the first month.  Vaccination is an effective method for taking infectious diseases under control but adhering to personal protective measures still maintains their importance.